2019
DOI: 10.1016/j.bone.2018.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between vertebral bone microstructure and estimated strength in elderly women: An ex-vivo HR-pQCT study of cadaveric spine

Abstract: Keywords:High-resolution peripheral quantitative computed tomography (HR-pQCT) Bone microstructure Estimated bone strength Vertebral body A B S T R A C TPurpose: A vertebral fracture is the most common complication of osteoporosis, and various factors are involved in its occurrence. The purpose of this study was to investigate the role of trabecular and cortical bone microstructure on vertebral strength using high-resolution peripheral quantitative computed tomography (HR-pQCT). Methods: Three female cadaveric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 40 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…The micro-CT system can calculate the density of the selected three-dimensional ROIs, and the BV/TV can be calculated based on the three-dimensional reconstruction of voxels. Yamada et al 23 have used high-resolution 3D micro-CT to study the microstructure of lumbar vertebrae. The BV/TV was closely related to the vertebral strength in their compression destruction experiment.…”
Section: Discussionmentioning
confidence: 99%
“…The micro-CT system can calculate the density of the selected three-dimensional ROIs, and the BV/TV can be calculated based on the three-dimensional reconstruction of voxels. Yamada et al 23 have used high-resolution 3D micro-CT to study the microstructure of lumbar vertebrae. The BV/TV was closely related to the vertebral strength in their compression destruction experiment.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] The micro-CT system can calculate the density of the selected 3D ROI, and the trabecular volume fraction can be calculated based on 3D reconstruction of voxels. Yamada et al [15] used high-resolution 3D micro-CT to study the microstructure of the lumbar spine and measure the volume fraction of the bone trabecula. It was found that high-resolution 3D assessment of the normal lumbar spine helped to better clarify the microstructure changes.…”
Section: Discussionmentioning
confidence: 99%
“…Bone microstructure imaging can accurately re ect the changes of bone microstructure at an early stage, which is both helpful for the investigation of the microstructure mechanism of osteoporosis and the subsequent evaluation of the e cacy of interventional therapy. In recent years, many scholars have studied the relationship between bone microstructure parameters and bone strength to obtain bone microstructure indicators that are most relevant to fracture risk [15][16][17]. However, these results were often contradictory to each other, which might be related to the different samples, measurement sites and experimental methods adopted.…”
Section: Introductionmentioning
confidence: 99%